Tumor risks of finerenone in patients with type 2 diabetes mellitus complicated with chronic kidney disease: a meta-analysis and systematic review of randomized controlled trials - Du, Yue; Cao, Gui; Gu, Linlin; Chen, Yuehong; Liu, Jingyu (Frontiers in Pharmacology, 2024)
Introduction: This study aimed to assess the tumor risk of finerenone in individuals with type 2 diabetes mellitus (T2DM) aggravated by chronic kidney disease (CKD). Methods: A thorough search in the OVID Medline, OVID EMBASE, and Cochrane Library databases from their creation through 2 November 2022 yielded randomized controlled trials (RCTs) reporting on the tumor risks of finerenone in patients with T2DM complicated with CKD. A pair of reviewers selected the relevant studies based on selection criteria, collected data, and assessed the methodological quality of eligible RCTs. The Peto odds ratio (OR) with a 95% confidence interval (CI) was calculated, and subgroup analysis of tumor nature, tumor origin system, tumor origin organ, and follow-up time was performed. Furthermore, Egger’s test was implemented to determine publication bias. Results: Four RCTs with 14,875 participants who had a low-to-moderate risk of bias were included. Compared with placebo treatment, finerenone did not increase the risk of overall neoplasms (Peto OR = 0.97; 95% CI, 0.83–1.14), malignant neoplasms (Peto OR = 1.03; 95% CI, 0.86–1.23), benign neoplasms (Peto OR = 0.94; 95% CI, 0.50–1.80), or in situ neoplasms (Peto OR = 0.14; 95% CI, 0.01–2.17). Subgroup analysis of the tumor origin system showed that finerenone was associated with an increased risk of malignant neoplasms of urinary tract compared with placebo treatment (Peto OR = 1.69; 95% CI, 1.07–2.67). The results were found to be robust in sensitivity analysis, and there was no indication of publication bias. Discussion: Finerenone is not associated with an increased risk of overall tumors, but it may be linked to an increased risk of malignant neoplasms in urinary tract. Additional well-planned cohort studies in larger research populations are needed to corroborate these findings. Systematic Review Registration:https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42022374101, Identifier CRD42022374101.